Electronic states of j-aggregates and of crystals of amphiphilic anthropyrimidine dye - Piryatinskii, YU.; Antypov, I.; Tarasenko, S.; Yatsun, O. (Energy and Automation, 2025)
Electronic spectra of crystals as well as of Langmuir-Blodgett films of amphiphilic derivative of anthropyrimidine dye were studied in the article. Reflection and time-resolved fluorescence spectra of LB-films were compared with polarized reflection and fluorescence spectra of dye’s crystals. Fluorescence spectra of films show eximer-like conformations with typical dependence between Stox’s-shift of spectral pick and fluorescence life-time. In crystals, these conformations are realized already in basic state. Similarity of crystal’s and of LB-film’s spectra points out that the arrangement of excited dye’s molecules along the long axis of J-aggregate is similar to molecular packaging in crystal along b-crystallographic direction. It was estimated the minimal quantity of molecules in J-aggregate. Key words: nano-size organic dye crystals, Langmuir-Blodgett films, J-aggregates, association of dye molecules, enhancement of electronic properties of aggregated dye molecules, seft-assembling of molecules